PENGARUH ESG DISCLOSURE DAN KUALITAS AUDIT TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Muhammad Hassan Septiyan; Surya Raharja (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the influence of ESG disclosure and audit quality on the value of companies in the mining sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. ESG is an important approach in assessing business sustainability, while audit quality reflects the reliability and credibility of a company's financial statements in the eyes of investors.This study used a quantitative approach with purposive sampling and secondary data obtained from Bloomberg and company annual reports. The independent variables consisted of ESG Disclosure and Audit Quality, while firm value was proxied by the Tobin's Q ratio. Data analysis was performed using multiple linear regression.The results show that ESG Disclosure has a positive and significant effect on firm value, indicating that sustainability disclosure can improve market perception of the company. However, audit quality does not have a significant effect on firm value, suggesting that auditor reputation alone may not be sufficient to influence market valuation in this sector during the observed period.